Influence of Chrysoporthe deuterocubensis canker disease on 2 the machining properties of Eucalyptus urograndis - Dahali, Rasdianah; Lee, Seng Hua; Md. Tahir, Paridah; Bakar, Edi Suhaimi; Muhammad Roseley, Adlin Sabrina; Ibrahim, Siti Aminah; Mohd Yusof, Norwahyuni; Mohammad Suffian James, Redzuan (Multidisciplinary Digital Publishing Institute, 2022)
This study assessed the machining properties of 11-year-old Eucalyptus urophylla × E. grandis, known as E. urograndis wood, that was infected by stem canker disease, Chrysoporthe deuterocubensis. Instead of being discarded directly, the study aimed to explore the possibility of infected trees being used in other applications such as furniture. Sawing, planing, and boring properties as well as the surface roughness of the healthy and infected trees were evaluated. The samples were collected from infected and healthy trees and classified according to the severity of the attack: healthy (class 1), moderately infected (class 2), severely infected (class 3), and very severely infected (class 4). Prior to sawing, planing, and boring, the samples were prepared according to ASTM D 1666-11 Standard Test Methods for Conducting Machining Tests of Wood and Wood-Base Materials. All samples were sawn, planed, and bored and were evaluated for their respective machining quality. The surface roughness of the machined samples was also assessed. Overall, E. urograndis of different infection severity has very good machining properties ranging from Grade I to III. Fuzzy grain, chip grain, chip mark, and tear out are the most commonly seen physical defects. As for surface roughness, healthy trees have lower surface roughness compared to that of infected trees, which indicates a better surface quality. The findings of this study suggested that infected E. urograndis can still be used in many applications. The results of this study will provide us with better knowledge about the machining performance of disease-infected E. urograndis wood and its possibilities to be used as raw material for the wood products industry.